Range of tax responsibility of heirs and ordinary legatees – an outline of the issues - Babiarz, Stefan (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
This study provides an introduction to the legal succession model of heirs and legatees in tax law. The author presents this model referring to the normative context and the interpretation of law, including judicature in this matter. He indicates the conditions that must be met in order for the situation in question to comply with standards of the constitutional protection of property rights and inheritance law.